Detrital clay grain coats in estuarine clastic deposits: origin and spatial distribution within a modern sedimentary system, the Gironde Estuary (south‐west France). Issue 3 (24th October 2018) - Virolle, Maxime; Brigaud, Benjamin; Bourillot, Raphaël; Féniès, Hugues; Portier, Eric; Duteil, Thibault; Nouet, Julius; Patrier, Patricia; Beaufort, Daniel
Abstract: Porosity and permeability may be preserved in deep sandstone reservoirs by clay coating (mainly chlorite) which limits quartz overgrowths. Chloritization around quartz grains results mainly from mineralogical transformations of pre‐existing clays. It is fundamental to study those clay precursors to better understand and predict the location and distribution of clay coatings in subsurface sandstones for petroleum or geothermal prospecting. This paper reports a high‐resolution analysis of the composition, distribution and fabric of clays along a modern estuary, the Gironde (south‐west France). The scale of the study ranges from thin sections, through sand bar bodies, up to the entire estuary. Results show that clays are detrital and deposited at the same time as sand grains despite strong hydrodynamic conditions. Clays bind to medium‐grained sands forming detrital clay grain coats. On average, 26% of detrital sand grains are coated along the entire length of the estuary. Coat thickness varies from 1 μm to more than 200 μm, and coat coverage exceeds 30% in some samples. The turbidity maximum zone position (surface water turbidity from 1 to 10 g l −1 ) in the estuary, which is controlled by seasonal variations in hydrodynamic processes, significantly impacts the location of the maximum clay content and the abundance of coated grains in sandy facies along the estuary. Flocculation in the water column results in the accumulation of suspended matter and contributes to the high turbidity in the estuary. Exopolymeric substances produced by diatoms are observed both in the field and by cryo‐scanning electron microscopy, suggesting that they may play a major role in binding detrital clay around sand grains. Finally, tidal bars and heterolithic point bars in the estuary funnel and estuarine channels are prime sedimentological targets for finding clay coatings and potentially good reservoir quality in deeply buried sandstones.